Cholera Toxins: Immunogenicity of the Rabbit Ileal Loop Toxin and Related Antigens - Kaur, Jasbir (1969)
A method of assay of immunogenic potency of the cholera gut toxin is described; it is based on the relation of dose of antigen to neutralizing antibody titer produced in the rabbit under defined conditions and allows quantification of immunogenicity as immunogenic units per milligram of protein. Evidence, based on immunogenicity and rabbit ileal loop toxicity, is presented which indicates that the positively charged fraction of liquid-culture supernatant fluid eluted in deionized water from diethylaminoethyl Sephadex, or in electrolyte from carboxymethyl Sephadex, is a complex made up of a nonantigenic toxic moiety, a nontoxic protein component which elicits the formation of toxin-neutralizing antibody, and an inactive fraction. The complex may also be dissociated in high-salt concentrations with apparent recombination of the toxic moiety with a nondialyzable constituent of peptone to give a negatively charged complex. The immunogenic component is found in nontoxic supernatant fluids of cultures grown at pH 6.5 or in media deficient in peptone. It is also present in the nontoxic fraction eluted from diethylaminoethyl Sephadex in electrolyte or in deionized water from carboxymethyl Sephadex. When separated from the positively charged toxic moiety, the net charge of the antigen is reduced as shown by immunoelectrophoresis. On primary fractionation, the antigen may be associated with a minor antigenic component of the negatively charged complex containing a major antigen eliciting vibriocidal antibody formation, but antisera to the toxin antigen preparations, either in this form or freed of antigenic contamination by recycling, do not contain vibriocidal antibody. It is suggested that this antigen be designated the T (toxin) antigen, and the antigen producing vibriocidal antibody the V antigen. These two antigens would appear to represent the major antigenic specificities associated with the antitoxic and antibacterial elements of the immune response to infection.